Non-governmental organisations and education for sustainable development : two case studies in Iceland - Drífa Guðmundsdóttir 1983- (2013)
The subject of this study is the role of two non- governmental organisations (NGOs), the Red Cross in Iceland and the Icelandic Church Aid, in promoting education for sustainable development. It is an exploration of whether, and how, the work of NGOs facilitates learning for sustainability. The research framework was developed by consulting theories and research literature on education, human rights, sustainable development, the work of NGOs and evidence of educational actions for sustainable development in the work done by NGOs. The aim of the research project was to explore the way these NGOs work, to consider whether they support bottom-up or top-down development, whether learning is promoted, and what might be learnt from them with regard to UNESCOs’ ideas of education for sustainable development. A qualitative approach was used, drawing on interview data and document analysis. Four individuals were interviewed, two employees and two volunteers from each NGO. The NGO specialist reports and annual reports were analysed. The main findings of the study are that life-long learning and formal, non-formal and informal education is sustained by the NGOs which prompt cooperation among people and organisations. The NGOs promote democratic behaviour and have a transformative influence on participants, including volunteers and the environment. The findings from the study also show that these two NGOs strengthen the voice of minority groups, influence authorities and promote bottom up development and learning. Key words: Education for sustainable development; NGOs; international education; sustainable development. Rannsókn þessi fjallar um hlutverk frjálsra félagasamtaka í ferli menntunar til sjálfbærrar þróunar á Íslandi, nánar til tekið Rauða Kross Íslands og Hjálparstarfs kirkjunnar. Rannsóknin byggir á fræðum og rannsóknum um frjáls félagasamtök og menntun til sjálfbærrar þróunar, sem er ekki innan hefðbundins ramma skóla. Leitast var við að kanna á hvaða hátt þessi félagasamtök vinna, hvort frekar sé unnið frá ...